Association between Lifetime Physical Activity and Cognitive Functioning in Middle-Aged and Older Community Dwelling Adults: Results from the Brain in Motion Study. (19th November 2015) - Gill, Stephanie J.; Friedenreich, Christine M.; Sajobi, Tolulope T.; Longman, R. Stewart; Drogos, Lauren L.; Davenport, Margie H.; Tyndall, Amanda V.; Eskes, Gail A.; Hogan, David B.; Hill, Michael D.; Parboosingh, Jillian S; Wilson, Ben J.; et al.
Abstract: To determine if total lifetime physical activity (PA) is associated with better cognitive functioning with aging and if cerebrovascular function mediates this association. A sample of 226 (52.2% female) community dwelling middle-aged and older adults (66.5±6.4 years) in the Brain in Motion Study, completed the Lifetime Total Physical Activity Questionnaire and underwent neuropsychological and cerebrovascular blood flow testing. Multiple robust linear regressions were used to model the associations between lifetime PA and global cognition after adjusting for age, sex, North American Adult Reading Test results (i.e., an estimate of premorbid intellectual ability), maximal aerobic capacity, body mass index and interactions between age, sex, and lifetime PA. Mediation analysis assessed the effect of cerebrovascular measures on the association between lifetime PA and global cognition. Post hoc analyses assessed past year PA and current fitness levels relation to global cognition and cerebrovascular measures. Better global cognitive performance was associated with higher lifetime PA ( p =.045), recreational PA ( p =.021), and vigorous intensity PA ( p =.004), PA between the ages of 0 and 20 years ( p =.036), and between the ages of 21 and 35 years ( p <.0001). Cerebrovascular measures did not mediate the association between PA and global cognition scores ( p >.5), but partially mediated the relation between current fitness and global cognition. This study revealed significant associations between higher levels of PA (i.e., total lifetime, recreational, vigorous PA, and past year) and better cognitive function in later life. Current fitness levels relation to cognitive function may be partially mediated through current cerebrovascular function. ( JINS, 2015, 21, 816–830)